2021
DOI: 10.21240/mpaed/40/2021.01.28.x
|View full text |Cite
|
Sign up to set email alerts
|

Hochschullehre im Pandemiebetrieb

Abstract: Im Sommersemester 2020 beteiligten sich 3469 Studierende sächsischer Hochschulen an einer Onlinebefragung zum Studium während der Coronapandemie. Trotz Campusschliessungen konnten die Befragten ihr Studium weitgehend wie geplant fortführen. Während die technische Ausstattung der Studierenden eine Teilnahme an digitalen Lehrveranstaltungen zuliess, zeigten sich Defizite bei der Qualität der Internetverbindung. Im Vergleich zum Vorsemester wurden die Studienorganisation als moderat (d = -0.48, 95 % CI [-0.52, -0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
1
0
0
2
Order By: Relevance
“…Our study reveals that the identified student subgroupsproponents, pragmatists and scepticsinherently reflect the changed circumstances of the mandatory digitalisation in teaching and learning as expressions of digital inequalities (Schmölz et al, 2020). Similar results with different wording were found in other studies investigating larger and smaller samples of students (Küsel et al, 2020;Karapanos et al, 2021).…”
Section: Data Analysis Results and Discussionsupporting
confidence: 91%
“…Our study reveals that the identified student subgroupsproponents, pragmatists and scepticsinherently reflect the changed circumstances of the mandatory digitalisation in teaching and learning as expressions of digital inequalities (Schmölz et al, 2020). Similar results with different wording were found in other studies investigating larger and smaller samples of students (Küsel et al, 2020;Karapanos et al, 2021).…”
Section: Data Analysis Results and Discussionsupporting
confidence: 91%
“…Numerous studies were conducted in the summer semester 2020 in Germany at various university locations and also nationwide, looking at the study situation during the first semester in the Corona pandemic. They show that in many places the transition from face-to-face to digital teaching initially went well (Berghoff et al, 2020;Karapanos et al, 2021;Kreidl & Dittler, 2021). However, students do not always find it easy to keep in touch with their fellow students or to organize their day with more personal responsibility (Marczuk et al, 2021;Traus et al, 2020).…”
Section: Study Conditions In Germany In Times Of the Corona Pandemicmentioning
confidence: 99%
“…For example, this can be associated with more required independence and a simultaneously increased workload, for example due to a more time-consuming processing of the accruing learning material (Adam-Gutsch et al, 2021;Feucht et al, 2020;Kreidl & Dittler, 2021). Students also state that they are more often distracted from their studies at home, that they have difficulty concentrating and that they are less able to organise themselves (Karapanos et al, 2021;Kreidl & Dittler, 2021;Marczuk et al, 2021;Traus et al, 2020). Looking at student satisfaction with digital learning opportunities, a very heterogeneous picture emerges.…”
Section: Study Conditions In Germany In Times Of the Corona Pandemicmentioning
confidence: 99%
“…Die Umstellung der Lehr-Lern-Settings von Präsenz auf Online war mit diversen Herausforderungen verbunden. Wenngleich viele Studierende über ein internetfähiges Endgerät verfügten, waren stabile Internetverbindungen sowie weitere technische Hürden (Stichwort Ausstattung) nach wie vor häufig problematisch (Adam-Gutsch, Paschel, Ophardt & Huck, 2021 ;Breitenbach, 2021 ;Karapanos, Pelz, Hawlitschek & Wollersheim, 2021). Weiterhin wurde zwar die Flexibilität des Arbeitens und selbständigen Lernens in der digitalen Lehre durch die Studierenden häufig positiv hervorgehoben, gleichzeitig nahmen sie aber auch einen erhöhten Workload und vermehrte Belastung wahr (Adam-Gutsch et al, 2021 ;Breitenbach, 2021 ;Karapanos et al, 2021).…”
unclassified
“…Wenngleich viele Studierende über ein internetfähiges Endgerät verfügten, waren stabile Internetverbindungen sowie weitere technische Hürden (Stichwort Ausstattung) nach wie vor häufig problematisch (Adam-Gutsch, Paschel, Ophardt & Huck, 2021 ;Breitenbach, 2021 ;Karapanos, Pelz, Hawlitschek & Wollersheim, 2021). Weiterhin wurde zwar die Flexibilität des Arbeitens und selbständigen Lernens in der digitalen Lehre durch die Studierenden häufig positiv hervorgehoben, gleichzeitig nahmen sie aber auch einen erhöhten Workload und vermehrte Belastung wahr (Adam-Gutsch et al, 2021 ;Breitenbach, 2021 ;Karapanos et al, 2021). [2] Die Veränderung der äußeren Rahmenbedingungen führte zu einem Aufbrechen von Lehrformaten und ermöglichte, beispielsweise durch den Einsatz digitaler Tools, offenerer Lehr-Lernformate, einer vielfältigeren Materialauswahl und flexibleren Abgabefristen eine stärkere Orientierung an den individuellen Voraussetzungen und Bedürfnissen aller Lernenden.…”
unclassified